2005
DOI: 10.1080/10401230590905344
|View full text |Cite
|
Sign up to set email alerts
|

Current Patterns and Future Directions in the Treatment of Insomnia

Abstract: There is evidence that improved sleep may improve outcome in some medical and psychiatric illnesses. Both behavioral and pharmacologic therapies have shown efficacy in chronic insomnia. In addition, a recent 6-month, randomized, controlled study has demonstrated that at least one agent may be safe and effective in longer-term use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…5 Sleep disturbance is a common symptom of depression and can be alleviated with antidepressants. 22 Participation in physical activity leads to reductions in depressive symptomology 23 and as a result might also improve sleep. Additionally, in menopausal women, poor sleep quality has also been linked to vasomotor symptoms, 13,24 although rather than causing sleep disturbance, hot flashes appear to coincide with arousals and awakenings.…”
mentioning
confidence: 99%
“…5 Sleep disturbance is a common symptom of depression and can be alleviated with antidepressants. 22 Participation in physical activity leads to reductions in depressive symptomology 23 and as a result might also improve sleep. Additionally, in menopausal women, poor sleep quality has also been linked to vasomotor symptoms, 13,24 although rather than causing sleep disturbance, hot flashes appear to coincide with arousals and awakenings.…”
mentioning
confidence: 99%
“…Studies have shown that benzodiazepines increases total sleep time but has no significant effect on sleep latency. Side effects of benzodiazepines include daytime sleepiness, hangover effects, dizziness, and impaired memory (Winkelman, & Pies, 2005). Furthermore patients taking benzodiazepines even for just a few days may develop dependence to the drug and thus patients may suffer withdrawal symptoms upon discontinuation of use (Passarella, & Duong, 2008).…”
Section: Pharmacological Approachesmentioning
confidence: 99%
“…Ramelteon is primarily used for the treatment of insomnias characterized by delayed sleep onset although evidence indicates that it also increases total sleep time (Passarella, & Duong, 2008). Common side effects associated with ramelteon include fatigue and dizziness (Winkelman, & Pies, 2005).…”
Section: Pharmacological Approachesmentioning
confidence: 99%
“…Tolerance is often cited as a potential concern when hypnotic medications are administered nightly beyond a short period of time (Winkelman and Pies, 2005). However, tolerance to the hypnotic effects of BzRAs has not developed in the vast majority of studies of hypnotic efficacy, most of which have been 4-12 weeks in duration, with a few examining 3-6 months of nightly use.…”
Section: Efficacy/effectiveness Of the Bzrasmentioning
confidence: 99%